A brief history of the future [videorecording (DVD)] - Morgan, Andrew (Filmmaker) (PBS Distribution, 2024)
Renowned futurist Ari Wallach invites viewers on a journey around the world that is filled with discovery, hope, and possibility about where we find ourselves today and what could come next. This series challenges the dystopian framework embraced by popular culture by offering a refreshing take on the future. The docuseries asks us all: how can we become the great ancestors the future needs us to be? "A Brief History of the Future" weaves together history, science, and unexpected ideas to expand our understanding about the impact that the choices we make today will have on our tomorrows.